2006
DOI: 10.1523/jneurosci.2575-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Stromal-Derived Factor-1 (CXCL12) Regulates Laminar Position of Cajal-Retzius Cells in Normal and Dysplastic Brains

Abstract: Normal brain development requires a series of highly complex and interrelated steps. This process presents many opportunities for errors to occur, which could result in developmental defects in the brain, clinically referred to as malformations of cortical development. The marginal zone and Cajal-Retzius cells are key players in cortical development and are established early, yet there is little understanding of the factors resulting in the disruption of the marginal zone in many types of cortical malformation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
111
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(118 citation statements)
references
References 48 publications
5
111
2
Order By: Relevance
“…In this study, we have shown that Sema3E has the capacity to modulate the migration of PlexinD1-positive CR cells triggered by CXCL12/CXCR4 signalling 17,18 . Chemokine signalling through CXCL12/CXCR4 is a common mechanism controlling the migration of several cell types along the body axis, such as hematopoietic progenitor cells 40 , vascular endothelial cells 41 , melanocytes 42 and tumour cells 43,44 .…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…In this study, we have shown that Sema3E has the capacity to modulate the migration of PlexinD1-positive CR cells triggered by CXCL12/CXCR4 signalling 17,18 . Chemokine signalling through CXCL12/CXCR4 is a common mechanism controlling the migration of several cell types along the body axis, such as hematopoietic progenitor cells 40 , vascular endothelial cells 41 , melanocytes 42 and tumour cells 43,44 .…”
Section: Discussionmentioning
confidence: 68%
“…Sema3E/PlexinD1 modulates CXCL12/CXCR4 signalling. It is well established that CR cell migration is promoted by CXCL12/ CXCR4 signalling 17,18 . Thus, we aimed to determine whether Sema3E/PlexinD1 might modulate the chemokine signalling (Fig.…”
Section: Sema3e or Plexind1 Absence Increased Cr Cells Migrationmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that similar molecular mechanisms might govern tangential migration in the IZ for both GABAergic and CP transient neurons. Indeed, in the MZ, similar cues have been shown to control the migration of GABAergic and CR cells, namely the CXCL12/CXCR4 pathway (Stumm et al, 2003;Borrell and Marín, 2006;Paredes et al, 2006). However, in contrast to GABAergic and CR neurons, CP transient neurons do not appear to be prevented to enter the CP.…”
Section: Focal Origins Of Glutamatergic Cortical Neurons and Tangentimentioning
confidence: 99%
“…The expression patterns for SDF-1 and CXCR4 in the developing DG, as well as the phenotype of CXCR4 knockout mice, are consistent with a model in which SDF-1 is secreted by meningeal cells that line the route of migrating CXCR4 expressing progenitors, and that progenitors are stalled in their migration when CXCR4 signaling is interrupted. Other neuronal phenotypes observed in CXCR4 knockout mice include defects in the placement of developmentally important Cajal-Retzius cells (Berger et al, 2007;Paredes et al, 2006;Stumm et al, 2003), cortical GABAergic interneurons (Stumm et al, 2007;Stumm et al, 2003;Tiveron et al, 2006) and GnRH secreting forebrain neurons (Schwarting et al, 2006). In all of these situations it appears that the progenitors for these neurons utilize SDF-1 mediated chemoattraction to attain their final positions, and that lack of CXCR4 signaling results in interrupted progenitor migration.…”
Section: Development Of the Nervous Systemmentioning
confidence: 99%